Follow-Up Study to Assess the Use and Performance of Household Filters in Zambia - Peletz, Rachel (The American Society of Tropical Medicine and Hygiene, 2013)
Effective household water treatment can improve drinking water quality and prevent disease if used correctly and consistently over time. One year after completion of a randomized controlled study of water filters among households in Zambia with children < 2 years old and mothers who were human immunodeficiency virus (HIV)-positive, we conducted a follow-up study to assess use and performance of new filters distributed at the conclusion of the study; 90% of participating households met the criteria for current users, and 75% of participating households had stored water with lower levels of fecal contamination than source water. Microbiologically, the filters continued to perform well, removing an average of 99.0% of fecal indicator bacteria. Although this study provides some encouraging evidence about the potential to maintain high uptake and filter performance, even in the absence of regular household visits, additional research is necessary to assess whether these results can be achieved over longer periods and with larger populations.